Oral Ulceration - McGuckin Bronagh; Swinson Brian (International Journal of General Practice, 2023)
Oral ulceration is a common disorder of the oral mucosa with individuals regularly presenting to primary care practitioners seeking advice and treatment. Diagnosis of oral ulceration remains a challenge for clinicians due to the overlap in clinical presentations and the diverse aetiological processes that can be involved in their development. A recent study evaluating general medical practitioners’ attitudes towards oral examination identified problems in clinicians’ confidence in differentiating between benign and malignant ulcers, with a lack of knowledge and training being cited as contributing factors. This article aims to provide an overview of the diagnosis and management of oral ulceration, providing a framework to guide clinical decision-making in a primary care setting.
Keywords: Ulcer